2016
DOI: 10.1080/15592294.2016.1192736
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic dysregulation in the developing Down syndrome cortex

Abstract: Using Illumina 450K arrays, 1.85% of all analyzed CpG sites were significantly hypermethylated and 0.31% hypomethylated in fetal Down syndrome (DS) cortex throughout the genome. The methylation changes on chromosome 21 appeared to be balanced between hypo- and hyper-methylation, whereas, consistent with prior reports, all other chromosomes showed 3–11 times more hyper- than hypo-methylated sites. Reduced NRSF/REST expression due to upregulation of DYRK1A (on chromosome 21q22.13) and methylation of REST binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 75 publications
(98 reference statements)
14
73
0
Order By: Relevance
“…4,5 The phenotype in Down syndrome is thought to arise from the overexpression and dysregulation of these genes and their associated pathways, together with global cellular stress responses and compensatory mechanisms early in development. 6 Epigenetic changes have also been observed in the fetal brain and blood from newborn infants with Down syndrome 7,8 which may further impact development and contribute to the range of observed cognitive outcomes. The neurological phenotype constantly changes over the life span of Down syndrome, 9 with differences continuing into adulthood.…”
Section: Chdmentioning
confidence: 99%
“…4,5 The phenotype in Down syndrome is thought to arise from the overexpression and dysregulation of these genes and their associated pathways, together with global cellular stress responses and compensatory mechanisms early in development. 6 Epigenetic changes have also been observed in the fetal brain and blood from newborn infants with Down syndrome 7,8 which may further impact development and contribute to the range of observed cognitive outcomes. The neurological phenotype constantly changes over the life span of Down syndrome, 9 with differences continuing into adulthood.…”
Section: Chdmentioning
confidence: 99%
“…Both of these neurodevelopmental disorders are characterized by defective dendritic arborization, abnormal synaptic formation, and disrupted dendritic spine morphology [163-165]. Microarray studies have uncovered hypermethylation of Pcdhg genes and promoters at multiple developmental stages in DS tissues including several brain regions [166,167]. Bisulfite pyrosequencing confirmed that multiple Pcdhg A and B subfamily gene promoters were hypermethylated in DS samples, and targeted RNA sequencing showed that this hypermethylation was, indeed, correlated with lower Pcdhg gene expression [167].…”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%
“…Microarray studies have uncovered hypermethylation of Pcdhg genes and promoters at multiple developmental stages in DS tissues including several brain regions [166,167]. Bisulfite pyrosequencing confirmed that multiple Pcdhg A and B subfamily gene promoters were hypermethylated in DS samples, and targeted RNA sequencing showed that this hypermethylation was, indeed, correlated with lower Pcdhg gene expression [167]. Though it remains to be demonstrated that reduced γ-Pcdh protein levels are causal for any of the dendritic or synaptic defects seen in DS, the phenotypes observed in Pcdhg null cortex (as discussed above, decreased dendrite arborization and altered dendritic spine number and morphology) are certainly consistent with such a possibility [54,82].…”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%
“…Another examination of DS fetal brain tissue (frontal and temporal cortex) observed a trend of modest global hypermethylation (0.3%) as well as hypermethylation of the clustered protocadherins, which are critical to neurodevelopment. 21 Interestingly, two separate studies of DS fetal frontal cortex have found that while significant DS-differential CpGs located on HSA21 displayed a balance of hypermethylation and hypomethylation, the significant CpGs across all other chromosomes were predominantly hypermethylated. 21,22 The DS differentially methylated CpGs belonged to genes involved in ubiquitin mediated proteolysis and Alzheimer's disease pathways.…”
Section: Introductionmentioning
confidence: 99%
“…21 Interestingly, two separate studies of DS fetal frontal cortex have found that while significant DS-differential CpGs located on HSA21 displayed a balance of hypermethylation and hypomethylation, the significant CpGs across all other chromosomes were predominantly hypermethylated. 21,22 The DS differentially methylated CpGs belonged to genes involved in ubiquitin mediated proteolysis and Alzheimer's disease pathways. 22 Taken together, the differences in CpG methylation observed across a variety of DS cells/tissues are not only relevant to early developmental events but also appear to be maintained into adulthood.…”
Section: Introductionmentioning
confidence: 99%